SINERGI SEKOLAH DAN ORANG TUA UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA DI SDN BANGKOK, BOYOLALI - Ristiya Krisnawati; Robith Khoiril Umam (Yayasan Pendidikan Literasi Borneo, 2025)
The role of parents in motivating their children to study is very important in the context of contributions related to academic achievement at elementary school. This study aims at describing the role of parents to improve their children’s learning motivation at SDN Bangkok, Boyolali. The research employs a qualitative approach using a case study method. Data are collected through observation, interviews, and questionnaires with parents and classroom teachers. The data analysis technique consisted of data reduction, data display, and conclusion drawing. The results show that most parents play a limited role in motivating their children to learn. This condition is influenced by several factors, including lack of time due to the fact that most parents work as street vendors and waste collectors, as well as limited understanding of their children’s school materials. In addition, many parents still assume that the responsibility for education lies entirely with the school. Through the synergy between the school and parents, awareness can be built that family involvement is essential in increasing students’ learning motivation and achievement. Parents are encouraged to spend time communicating with their children, provide moral support, and collaborate actively with teachers. Thus, economic limitations should not become a barrier for parents to contribute to their children’s educational success